Influence of Varying Fiber Length on the Mechanical and Physical Properties of Cement Bonded Fiberboard Containing Palm Empty Fruit Bunch - Ismail, Mimi Liyana; Nik Soh, Nik Mohd Zaini (Recent Trends in Civil Engineering and Built Environment, 2021)
Past few years, there has been continued interest in the use of natural plant fiber in cement composites as an alternative to traditional reinforcement. The use of fibers derived from plants into the fiberboard production has increased significantly. Not only because of it strengthen the mechanical features of cement bonded fiber board (CBFB), but they are also renewable, easy to obtain and inexpensive. A few samples of EFB cement boards are fabricated with different class of shredded Oil Palm Fiber length which is R30M, R14M and R7M which is to obtain the effect of the length of fiber to its properties. In this study the treatment used is NaOH with 0.4% concentration which to improve the workability of the fiber and the cement mixture. Oil Palm Fiber Board (OPFB) with different length of fiber which is 25.72 mm (R30M), 14.37 mm (R14M) and 4.32 mm (R7M) are produced. Thickness and density, Modulus of Rupture (MOR), Modulus of Elasticity (MOE) and Internal Bonding (IB) test are conducted in order to obtain the relationship of the fiber length towards the physical and mechanical properties of the composite. The role of fiber in this study is, it acts as a reinforcement for the cement board. The research findings indicate that the ideal fiber length that can be used for further research is from medium size EFB which is R14M. The tested sample shows that the Modulus of rupture (MOR), Modulus of elasticity and Internal bonding (IB) obtained are 161.2 N/mm2, 44.39 N/mm2and 0.402 N/mm2 respectively.